2012
DOI: 10.1111/j.1944-9720.2012.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Standards for Foreign Language Learning: Defining the Constructs and Researching Learner Outcomes

Abstract: In an effort to articulate an agenda for learner outcomes research linked to the Standards for Foreign Language Learning in the 21st Century, this review examines the profession's current conceptualization of the National Standards in research on learner outcomes across various levels of instruction. The research literature reviewed reveals that, to date, empirical studies of learner outcomes have been conducted only on the Communication goal of the National Standards. Consequently, in the majority of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 67 publications
(121 reference statements)
3
27
0
2
Order By: Relevance
“…Using a classification scheme such as Herring's () helps teachers take into account both the technological and social facets of CMD and directs the teacher's focus toward meaningful communication. Furthermore, it allows flexibility for lesson planning and supports the teacher's continued growth as new technologies emerge by providing both prospective and experienced teachers with a tool to examine CMD when designing technology‐mediated tasks, as suggested by Arnold () and Troyan ().…”
Section: Discussionmentioning
confidence: 99%
“…Using a classification scheme such as Herring's () helps teachers take into account both the technological and social facets of CMD and directs the teacher's focus toward meaningful communication. Furthermore, it allows flexibility for lesson planning and supports the teacher's continued growth as new technologies emerge by providing both prospective and experienced teachers with a tool to examine CMD when designing technology‐mediated tasks, as suggested by Arnold () and Troyan ().…”
Section: Discussionmentioning
confidence: 99%
“…Given the needs of standards-based instruction (Troyan, 2012), CBI , immersion education and CLIL (e.g., Gort, 2006Gort, , 2012Gort & Pontier, 2012), which has investigated the code switching that occurs in bilingual classrooms, for guidance in responding to this question. Certainly, a growing number of researchers in foreign language education have underscored that an awareness of the functions of language among language teachers is critical in enabling what Cammarata and Tedick (2012) refer to as a linguistic «awakening» (p. 260-261) as they become more aware of the demands of balancing content and language.…”
Section: Discussion 28mentioning
confidence: 99%
“…The genre theory informed by systemic functional linguistics (SFL, Halliday & Matthiessen, 2004 guided the development of the instructional intervention that the teacher implemented. This genre theory and SFL have been cited as a means for developing essential language awareness among language teachers (e.g., Gebhard, 2010;Troyan, 2012). The present study is part of a larger study of the design and implementation of a genre-based model of instruction, which has been described elsewhere (Troyan, 2014).…”
mentioning
confidence: 99%
“…For example, Rifkin () concluded that “two decades of guideline‐influenced instruction have failed to have an impact on student learning” (p. 582). For this reason, we require more work investigating the validity of these tools, following the lead of Dandonoli (), Norris and Pfeiffer (), Troyan (, ), and Tigchelaar, Bowles, Winke, and Gass (). If we are using those tools as indicators and starting points for goal‐setting, then we must validate them and identify their limitations in order to more effectively guide student language development.…”
Section: Defining Grand Challenges In Foreign Language Educationmentioning
confidence: 99%